Missed Opportunities for Immunization at The Out-Patient Clinic: Prevalence and Related Factors - Hafiz Abubakar; Ali Antoni; Johnwan Usman; Iskandar Z. Lubis; RA. Aggraini Erma (Indonesian Pediatric Society, 1996)
From November 1992 through Januaiy 1993 a cross sectional study was conducted to determine the prevalence and related factors of missed opportunities for immunization (MOI). The study involved 280 babies aged less than 12 months. Interview was performed by using a questionnaire as the babies left the clinic after seeing the clinic personnel (exit interview). The primary source of information was the accompanying person and their immunization card. There were 149 (53%) male and 131 (47%) female babies. A total of 208 babies (74.3%) stated to have immunization card, although only 19 (9.1°/.) look it at the time of the study. Out of 234 babies (83.5%) with partial immunization status, 9 had contraindication to immunization. Among 225 ba- es without contraindication, only 88 babies were suggested to have immunization. MOI was found in 137 (48.8%) babies (95% confidence interval: 43%; 55%). Concerning the kind of vaccine, OFV was the most often missed. Of 88 babies (31.4%) suggested for immunization, 43 agreed and had been given various vaccines including simultaneus immunization at the Well-Child Clinic. Screening for immunization not consistently practiced, missed interpretation to contraindication was detected. Among babies suggested for immunization, significant relationships were found between the number of children in the family (p<0.05), father's (p<0.05) and mother's education (p<0.001) and acceptance to immunization.